Bose-Einstein correlations in W+W- events at LEP2 - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, Z; Alderweireld, T; Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2005)
Bose-Einstein correlations (BEC) between final state particles in the reaction e+e- → W+W- → q1q2̄q3q4̄ have been studied. Data corresponding to a total integrated luminosity of 550 pb -1, recorded by the DELPHI detector at centre-of-mass energies ranging from 189 to 209 GeV, were analysed. An indication for inter-W BEC between like-sign particles has been found at the level of 2.4 standard deviations of the combined statistical and systematic uncertainties. © Springer-Verlag / Società Italiana di Fisica 2005.